Fantasies About the Earthly Paradise: Costa Rica as a Nature Tourist Destination in Two Promotional Postage Stamps - Cartagena Núñez, Catalina (2026)
Introduction: This paper studies the representations of Costa Rica as a tourist destination featured on two postage stamps launched by the Costa Rican Tourism Institute and Costa Rica Post Office in 2021. Objective: To analyze the postal issue emphasizing the way in which the images in question, beyond their openly promotional purposes, contribute to producing meanings regarding Costa Rica as a nature tourist destination. Methods: To do so, a content analysis was carried out based on the model proposed by Stuart Hall and Paul du Gay called the “circuit of culture”, which examines the portrayal of Costa Rican nature as an idyllic paradise free from social conflict, offering foreign visitors the fantasy of an idealized natural world. Results: The study identifies that the production of these tourist images relies on stereotypical representations that reduce diverse views of nature and cultural practices within the national territory, while also rendering local socio-spatial realities invisible. Conclusions: From this perspective, it is concluded that, despite their apparent innocuousness, postage stamps inform about the way in which the Costa Rican tourist experience is offered today for the rest of the world to see.